Pocket Pain and Neuromodulation: Negligible or Neglected?. Issue 6 (12th July 2017) - Dietvorst, Sofie; Decramer, Thomas; Lemmens, Robin; Morlion, Bart; Nuttin, Bart; Theys, Tom
Abstract : Objectives: Pain encountered at the site of the implantable pulse generator (IPG) after invasive neuromodulation is a well‐known and important complication. The reported incidence of implant site pain is variable, ranging between 0.4 and 35%. Implant site pain has never been systematically studied and no treatment guidelines are available. Material and Methods: We performed an observational study (study registration number mp05728) on the incidence and the determining factors of implant site pain, the subjective rating of intensity by sending questionnaires ( n  = 554) to our cohort of neuromodulation patients with IPGs. The number of revision surgeries and explants due to implant site pain were also analyzed. Results: Total response rate was 50% ( n  = 278). Pain patients suffered significantly ( p  < 0.05) more often from IPG site pain than other patients undergoing neuromodulation therapies. Up to 64% of patients undergoing spinal cord stimulation reported IPG site discomfort or pain. Severe pocket pain was found in up to 8% of patients. No association was found between other variables (age, BMI, duration of follow‐up, gender, smoking, number of pocket surgeries) and implant site pain. Conclusion: Pocket pain represents an important problem after invasive neuromodulation and is more prevalent in pain patients. We believe further technological improvements with miniaturized IPGs will impact the incidence of pocket pain and could even obviate the need for an IPG pocket.